Factors Associated with Arkansans’ First Use of Telehealth during the COVID-19 Pandemic - Jennifer A. Andersen; Holly C. Felix; Dejun Su; James P. Selig; Shawn Ratcliff; Pearl A. McElfish (International Journal of Telemedicine and Applications)
Objective. To examine the factors associated with the first use of telehealth during the COVID-19 pandemic using Andersen’s Model of Healthcare Utilization. Andersen’s Model of Healthcare Utilization allowed the categorization of the independent variables into the following: (1) predisposing factors, including sociodemographic variables and health beliefs; (2) enabling factors, including socioeconomic status and access to care; and (3) need for care, including preexisting or newly diagnosed conditions and reasons to seek out care or to utilize a new mode of care. Methods. Potential respondents (n=4,077) were identified for recruitment from a volunteer registry in Arkansas. Recruitment emails provided a study description, the opportunity to verify meeting the study’s inclusion criteria and to consent for participation, and a link to follow to complete the survey online. The online survey responses were collected between July and August of 2020 (n=1,137). Results. Telehealth utilization included two categories: (1) utilizers reported the first use of telehealth services during the pandemic, and (2) nonutilizers reported they had never used telehealth. Lower odds of reporting telehealth utilization during the pandemic were associated with race (Black; OR=0.57, CI [0.33, 0.96]) and education (high School or less; OR=0.45, CI [0.25, 0.83]). Higher odds of reporting telehealth utilization included having more than one provider (OR=2.33, CI [1.30, 4.18]), more physical (OR=1.12, CI [1.00, 1.25]) and mental (OR 1.53, CI [1.24, 1.88]) health conditions, and changes in healthcare delivery during the pandemic (OR=3.49, CI [2.78, 4.38]). Conclusions. The results illustrate that disparities exist in Arkansans’ utilization of telehealth services during the pandemic. Future research should explore the disparities in telehealth utilization and how telehealth may be used to address disparities in care for Black Arkansans and those with low socioeconomic status.